EVALUASI PURNA HUNI PADA PASAR BUJEL DI DESA BANJARSARI, KULONPROGO - Wirasmoyo, Wiliarto; Ratriningsih, Desrina; Haryanti, Indah Pradnya (Jurnal Arsitektur Komposisi, 2020)
The Bujel Market in Banjarsari Village, Kulonprogo, which is classified as a type D market, is only active from 1:00 to 6:00 am, after that there is no more buying and selling activities taking place. This Full Occupancy Evaluation (EPH) aims to find problems and potentials in the market by adjusting the functions and needs of users that emphasize the architectural aspects of the building and the behavior of its residents according to SNI for Pasar Rakyat. This study aims to revive the market area outside its operational hours and increase the market's function as an area for socializing, gathering, and making the market a supporting area for the activities of the village hall. The method used in this research is descriptive qualitative method with observations and interviews using the analysis of Post-Huni Evaluation (EPH) and the comparison of SNI to Pasar Rakyat. The results of this study provide recommendations for the market to be more active and develop properly according to SNI for the People's Market.